Records Committee review for rare bird sighting of Lesser Black-backed Gull at the Des Moines River in Des Moines, 1993 - Cecil, Robert I.et al (1993)
Records Committee review for a Lesser Black-backed Gull at the Des Moines River in Des Moines in Polk County, IA on December 21, 1993. Includes a record review document with votes and a documentation form submitted to the committee. Epson - sheet feed